Morphological, physiological, and biochemical characteristics of Physalis peruviana L. plants under different water availabilities - Lima, Ianna Kamyla Freitas; Nascimento, Marilza Neves do; Santana Guimarães, David; Santos Neto, Francisco dos; Gonçalves Neto, Lourival Palmeira (Comunicata Scientiae, 2024)
Growing Physalis peruviana, which is known for its nutraceutical potential and pleasantly sweet-tasting fruits, can be a profitable economic activity for many small-scale farmers across different regions of Brazil. Therefore, studying its agronomic performance under adverse conditions is necessary, mainly concerning low water availability, which is common during dry periods in semiarid areas in the Northeast region of Brazil. Thus, the objective of this study was to assess the effects of different water availability conditions (20%, 40%, 60%, 80%, and 100% of field capacity - FC) on Physalis peruviana plants. Morphological and physiological characteristics were evaluated: plant height, stem diameter, primary root length, number of leaves per plant, leaf area, relative water content, leaf water potential, and total dry weight. Biochemical analyses were conducted to determine the contents of total soluble proteins, total sugars, reducing sugars, sucrose, and total chlorophyll. Plants subjected to 20% of FC exhibited reduced height, stem diameter, number of leaves, leaf area, relative water content, and leaf water potential due to low soil water availability. Water stress caused an increase in contents of chlorophylls, total soluble proteins, total sugars, reducing sugars, and sucrose.